2007
DOI: 10.1136/gut.2005.090050
|View full text |Cite
|
Sign up to set email alerts
|

Functional integration of hepatocytes derived from human mesenchymal stem cells into mouse livers

Abstract: Aims: At present, clinical success of hepatocyte transplantation as an alternative to whole liver transplantation is hampered by the limited availability of suitable donor organs for the isolation of transplantable hepatocytes. Hence, novel cell sources are required to deliver hepatocytes of adequate quality for clinical use. Mesenchymal stem cells (MSCs) from human bone marrow may have the potential to differentiate into hepatocytes in vitro and in vivo. Methods: Isolated MSCs were selected by density gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
246
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(262 citation statements)
references
References 46 publications
12
246
0
4
Order By: Relevance
“…First, ESCs could generate functional hepatocytes in vivo that are then engrafted efficiently within the host liver 6. A study reported that 2.5%–5% is necessary for reversing the liver injuries 59. We also observed additional CM‐Dil + /ALB + cells in the GF‐PEI‐MSN complex group; however, low amounts of these cells could not significantly reverse the injured liver, which was mentioned by previous investigators 60.…”
Section: Resultsmentioning
confidence: 55%
“…First, ESCs could generate functional hepatocytes in vivo that are then engrafted efficiently within the host liver 6. A study reported that 2.5%–5% is necessary for reversing the liver injuries 59. We also observed additional CM‐Dil + /ALB + cells in the GF‐PEI‐MSN complex group; however, low amounts of these cells could not significantly reverse the injured liver, which was mentioned by previous investigators 60.…”
Section: Resultsmentioning
confidence: 55%
“…If human MSCs are xenografted to the allyl alcohol-damaged livers of immunosuppressed rats, large groups of human albumin-positive hepatocytes are generated without cell fusion being involved [105]. Transplanted human MSCs also contribute to the hepatocyte mass, predominantly periportally, in the partially hepatectomized livers of immunodeficient mice when regeneration is impeded by a β-receptor antagonist [106]. Human MSCs from adipose tissue, selected on the basis of CD105 (endoglin) expression, also generate hepatocytes when injected into nude mice at 24 h after CCl 4 injury [107].…”
Section: Bone Marrowmentioning
confidence: 99%
“…Recently, many studies have been conducted to investigate the hepatocyte differentiation properties of MSCs in response to various culture conditions. 6,7,28 Potential candidates include hepatocyte growth factor, epidermal growth factor, oncostatin M, and vascular endothelial growth factor, and these factors were therefore nominated as modulators of stem cell differentiation. 5,[29][30][31] However, the length of time required during hepatic differentiation of MSCs under prolonged exposure in the specific culture media is the major drawback.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A number of reports have suggested that MSCs from rat, mouse, and human can be induced to differentiate into functional hepatocyte-like cells and express certain distinct hepatocyte markers and provide functional support. [3][4][5][6][7] Although the capability of MSCs to differentiate into hepatocytes has been established, the precise underlying mechanism that regulates the differentiation process is still unclear.…”
mentioning
confidence: 99%